Blood biomarkers for estimating energy intake in Japanese male collegiate athletes: a pilot study - Kurosaka, Y.; Nagasawa, T.; Minato, K.; Hasegawa-Tanaka, T.; Naito, H.; Wakui, S.; Machida, S. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background Athletes should be informed of their required energy intake in preparation for sports competitions. However, the environment in which dietary surveys can be conducted to determine the required energy intake for sports competitions is limited, and such survey will require a substantial amount of time and effort from athletes and dietitians. If certain biomarkers for estimating the energy intake can be identified, they may compensate for the shortcomings of these dietary surveys. We aimed to identify the blood biomarkers to estimate the energy intake/basal metabolic rate ratio of male athletes.